ANALISIS KOINTEGRASI DAN KAUSALITAS TINGKAT PENGANGGURAN TERHADAP VARIABEL MAKRO DI INDONESIA - M. Satrio Al Ridho; Isnaini Harahap; Marliyah Marliyah (ITB AAS INDONESIA, 2023)
This study aims to analyze in depth the Contribution and Integration of Unemployment Rate, Inflation, Investment and Economic Growth. This research is a quantitative study and used Eviews 10 software. The Vector Auto Regression (VAR) analysis technique is used to see the relationship between the variables that are the choices in determining the unemployment rate in Indonesia. In this study using VAR in First Difference because the data is not Stationary at the level. Cointegration test, it indicates that these variables are cointegrated at the level < 5% so that there is a long-term relationship. Granger causality test results, there is a one-way causality relationship between INV to UNEMP, GDP to GROWTH, INF to GDP, and INF to GROWTH and two-way causality between INV and GROWTH. Based on long-term VECM estimates, GROWTH has a negative and significant effect, GDP and INV have a significant positive effect. In the short term, INF and INV have a negative and significant effect on the value of Adj. R-Square of 20.3%. Impulse Response Function analysis, GROWTH is a variable that experiences stability more quickly when shocks occur. Variance Decomposition, it turns out that UNEMP has the largest response and composition for other variables